Towards improving information quality requirements for online health information systems: A review on the recent frameworks - Ighe, Mohamed Aden; Mohammed, Siti Asma (Institute of Electrical and Electronics Engineers Inc., 2018)
The recent demand of accessing online health information has increased sharply due to the mass production of information and their value strongly depends on the quality of information that is inside the content of the system. However, many of the online health information portals provide poor information quality for its users, and the main reason is that the information quality requirements weren’t included at the earliest stages of the system development process. The objective of this research is to provide a literature review on frameworks that improves the implementation of information quality requirements. At least several recent papers were searched from various sources, between 2012 to 2017. The findings show that all frameworks include the information quality requirements during the earliest phases of the system development process through various methods, so mistakes are avoided during the ongoing stages of the process. The research gives a clear understanding for practitioners and administrators about the gaps in their content that should overcome and put into consideration. © 2018 IEEE.